The new quantum age : from Bell's theorem to quantum computation and teleportation - Whitaker, Andrew (Oxford University Press, 2012)
A clear account of what has been discovered in recent years about quantum theory, its counter-intuitive features - non-locality, indeterminism, intrinsic uncertainty - and what it tells us about the universe. The book also explains how these ideas have led to a new subject of limitless possibilities - quantum information theory.